Effect of free surface deformation on the extractable power of a finite width turbine array. (April 2016) - Vogel, C.R.; Houlsby, G.T.; Willden, R.H.J.
Abstract: The effect of free surface deformation on the power extracted by a tidal turbine array partially spanning a wide channel is investigated using a theoretical model. Two predominant flow scales are assumed; turbine-scale flow, and array-scale flow, which are analysed as quasi-inviscid open channel flow problems in which conservation of mass, momentum, and energy are considered, and coupled through kinematic and dynamic boundary conditions. Power extraction may be maximised by determining the optimum inter-turbine spacing, which also enhances efficiency (ratio of power generated to power removed from the flow). Power extraction and efficiency increase as Froude number increases, improving open channel array performance. In the infinitely wide channel limit, the extracted power depends only on Froude number and local blockage (ratio of turbine to local flow passage areas). At zero Froude number, the peak power coefficient increases from the Lanchester-Betz limit (0.593) to 0.798, occurring when the local blockage ratio is approximately 0.4. Froude numbers in the range of 0.1–0.2, typical of prospective tidal energy sites, increase the peak power coefficient by an additional 1%–4.5% when the array occupies a negligible fraction of the channel, increasing further as a greater proportion of the channel is occupied. Highlights: A multi-scale flow model past a turbine array in an open channel is proposed. Multi-scale model coupled through kinematic and dynamic boundary conditions. Peak power coefficient increases from Betz to 0.798 in an infinitely wide channel. Peak power coefficient increased by a further 1%–4.5% for typical Froude numbers. Peak power continues to increase with Froude number as array blockage increases.